Glutamate utilization promotes meningococcal survival in vivo through avoidance of the neutrophil oxidative burst. - Talà, A; Monaco, C; Nagorska, K; Exley, R; Corbett, A; Zychlinsky, A; Alifano, P; Tang, C (2011)
Polymorphonuclear neutrophil leucocytes (PMNs) are a critical part of innate immune defence against bacterial pathogens, and only a limited subset of microbes can escape killing by these phagocytic cells. Here we show that Neisseria meningitidis, a leading cause of septicaemia and meningitis, can avoid killing by PMNs and this is dependent on the ability of the bacterium to acquire L-glutamate through its GltT uptake system. We demonstrate that the uptake of available L-glutamate promotes N. meningitidis evasion of PMN reactive oxygen species produced by the oxidative burst. In the meningococcus, L-glutamate is converted to glutathione, a key molecule for maintaining intracellular redox potential, which protects the bacterium from reactive oxygen species such as hydrogen peroxide. We show that this mechanism contributes to the ability of N. meningitidis to cause bacteraemia, a critical step in the disease process during infections caused by this important human pathogen.